Understanding the Global TV Format - Moran, Albert; Malbon, Justin (Intellect Books, 2006)
This volume presents a series of papers concerned with the interrelations between the postmodern and the present state of art and design education. Spanning a range of thematic concerns, the book reflects upon existing practice and articulates revolutionary prospects potentially viable through a shift in educative thinking.
Keywords: 1-TV; 2-Analyses formalistes; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); _Nettoyé

Asia: New Growth Areas - Keane, Michael (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
The previous chapter introduced in broad brushstrokes the issues at stake in this study, beginning with a critique of globalization and moving on to sketch in ﬁner detail national television systems, the role of local content, and the economic importance of formats. The chapter concluded with a brief overview of the vagaries of copyright law as it applies to formats. Here, we initiate a discussion of Asian television systems beginning with a much different perspective on the ramiﬁcations of cultural borrowing. In this context we note that the format business straddles the divide between creative endeavour and innovation on the one hand, and slavish imitation on the other. This polarization manifests in widespread misunderstanding of the goals of format producers and distributors, and the role that formats play in the shaping of television schedules. We need therefore to ﬂesh out the in-between issues. These are primarily concerned with the relationship between the format and its localization, television consumption within ‘cultural continents’, and changes in media systems. Taking this further we note the relationship between production and reception within Asia, the growth of television industries in the region and the relationship between formatting and new media distribution platforms that use interactive technologies allowing viewers to feedback responses. This exercise enables us to identify an alternative list of conceptual tools to those championed by political economy scholars.
Num Pages: 12
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); _Nettoyé

Coping, Cloning and Copying: Hong Kong in the Global Television Format Business - Fung, Anthony (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Hong Kong is famous internationally as a ﬁnancial market, a shopping paradise, and Chinese ﬁlm production hub, but notoriously (and perhaps even attractively for some) Hong Kong is also a hotbed of piracy of computer software, DVDs, watches and toys.1 While many cultural products such as television dramas and movies are original and quite reputable in the region, media critics argue that the copycat phenomenon, which includes borrowing, inserting and modifying other cultural texts to augment local production, is common in the media and entertainment industries (Fung 1998). Whenever a new form, style, or popular culture trend emerges in Hong Kong, market forces soon kick in to replicate it. However, this kind of reproduction, as shown by the history of cultural production in Hong Kong, does not necessarily lead to a degradation of programme quality. Reproduction is not only a savvy strategy to reduce the ﬁnancial risks inherent to new products, but also aims at producing ‘improved’ versions which can reap more proﬁts for the industry.
Num Pages: 14
Keywords: 1-TV; 2-Analyses formalistes; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé

A Revolution in Television and a Great Leap Forward for Innovation?: China in the Global Television Format Business - Keane, Michael (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Unlike smaller nation-states in this study the People’s Republic of China has never really countenanced a scarcity of domestic television content. Supply has been constant, indicating both the importance and the sheer size of the sector. The nationalized broadcast media has for several decades churned out cheaply produced ﬁlms, documentaries, dramas, and news programmes. During the last two decades of the twentieth century, however, audience demand for domestic content began to wane as more as more international programmes found their way into schedules, particularly in southern China. China’s accession to the World Trade Organization in December 2001 seemed to herald soul-searching among its media mandarins. What would happen? Would China be inundated by foreign content (the worst case scenario) or would China, as it has done over time, absorb and regulate foreign inﬂuences?
Num Pages: 17
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Chine (corpus analysé); _Nettoyé

New Television, Globalisation, and the East Asian Cultural Imagination - Keane, Michael; Fung, Anthony Y. H.; Moran, Albert (Hong Kong University Press, 2007)
This volume is divided into three parts: 'Adaptation and Local Production in East Asia', 'Formats, Clones, and Generic Variations' and 'New Television'.
Keywords: 1-TV; 2-Analyses formalistes; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Chine (corpus analysé); Corée du Sud (corpus analysé); Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); Japon (corpus analysé); Taiwan (corpus analysé); _Nettoyé

Reformatting the Format: Philippines in the Global Television Format Business - Santos, Joseﬁna M. C. (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
In the eyes of many observers the Philippine cultural icon that is synonymous with travel, as well as being the subject of numerous advertisements is the jeepney, a public-transport vehicle assembled in the style of the US military jeep but lengthened to accommodate from fourteen to twenty-two sitting passengers. What distinguishes the jeepney from run-of-the-mill public transport however is its artistic décor: a clutter and kaleidoscope of various artefacts from miniature steel horses dotting the hood, to massive, jazzy plastic or steel billboards announcing the name of the jeepney, to murals painted in ﬁesta colours at the sides, to a bizarre combination of items in the front windshield juxtaposing conﬂicting images of the Sto. Nino (the baby Jesus Christ) and stickers with sexually risqué messages.
Num Pages: 12
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Philippines (corpus analysé); Philippines (lieu de production du savoir); _Nettoyé

Cloning, Adaptation, Import and Originality: Taiwan in the Global Television Format Business - Liu, Yu-Li; Chen, Yi-Hsiang (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Taiwan residents enjoy one of the most abundant television diets in East Asia. Eighty per cent of households subscribe to cable television services, offering a buffet of more than eighty channels including niche and full service channels. Taiwan’s television industry, while relatively small in comparison with its competitors in East Asia, has established a reputation for creatively re-generating formats developed elsewhere.
Num Pages: 20
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Taiwan (corpus analysé); Taiwan (lieu de production du savoir); _Nettoyé

Copied from Without and Cloned from Within: India in the Global Television Format Business - Thomas, Amos Owen; Kumar, Keval J. (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Television programme format adaptation is becoming an increasingly signiﬁcant phenomenon in India as it is in many other countries with an active domestic television industry. Some obvious successes stand out in recent years, such as Kaun Banega Crorepati, the licensed adaptation of Celador’s global format success Who Wants To Be A Millionaire?, and C.A.T.S., a licensed Hindi version of the US detective series Charlie’s Angels. However, sensitivity to local cultural nuances has been critical to their popular reception by Indian audiences. Yet despite a few high-proﬁle licensed adaptations or copycatting, there are far more instances of unlicensed adaptations or cloning, sometimes subtle, other times not.
Num Pages: 16
Keywords: 1-TV; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); Suède (lieu de production du savoir); _Nettoyé